A COMPARISON BETWEEN USUAL OFFICE AND FOUR OTHER METHODS TO EVALUATE BLOOD PRESSURE (BP-TRUE, HBPM, ABPM AND CBP) DURING 3 YEARS FOLLOW-UP. (June 2018) - Ruilope, L.-M.; Brotons, C.; Quevedo-Aguado, L.; Segura, J.; Martinez, P.; Ruiz-Hurtado, G.; Moral, I.; Calvo-Bonacho, E.
Abstract : Objective: Recently the methodology used to estimate blood pressure (BP) in the SPRINT study (3 measurements with an OMRON device with the patient isolated) has questioned the applicability of a goal of systolic BP below 120 mmHg. We have compared differences between 5 methods of BP measurements. Design and method: A total 615 patients with pre-diabetes (N = 431) and type 2 diabetes (N = 184) were included in the study. Office BP was estimated through 3 observed measurements. The other methods were: BP-TRUE (N = 184), HBPM (N = 431), ABPM (N = 615) and CBP (N = 615) used under the standard conditions. Patients were followed for 3 years during which serum creatinine, pulse wave velocity (PWV), and other biochemical parameters were analyzed Results: Office BP exhibited the highest and CBP the lowest values. At the end of follow-up, Office BP was 133 in pre-diabetic and 135 mmHg in diabetic patients that were 3 and 15 mmHg above at baseline. The Table shows the differences between methods in prediabetic and diabetic patients. A subtle but continuous rise was observed in serum creatinine and PWV during the follow-up of diabetics. Table. Differences between office systolic BP and the other methodologies in prediabetic and diabetic patients. Figure. No caption available. Conclusions: The 5 methods compared require the consideration of different BP goals to attain the maximal benefit of BP reduction. The best approach compared to office BP corresponds to ABPM and CBP followed by HBPM and BP-TRUE. Cardiorenal disease progresses in established diabetics with an acceptable BP control.